Theories of international relations contending approaches to world politics - Lawson, Stephanie (Polity, 2015)
"Since the field of International Relations was established almost a century ago, many different theoretical approaches have been developed, each offering distinctive accounts of the world, why it has come to be the way it is, and how it might be made a better place. In this illuminating textbook, leading IR scholar, Stephanie Lawson, examines each of these theories in turn, from political realism in its various forms to liberalism, Marxism, critical theory and more recent contributions from social theory, feminism, postcolonialism and green theory. Taking as her focus the major practical issues facing scholars of international relations today, Lawson ably shows how each theory relates to situations on the ground. Each chapter features case studies, questions for discussion to encourage reflection and classroom debate, guides to further reading and web resources. The study of IR is a profoundly normative enterprise, and each theoretical school has its strengths and weaknesses. Theories of International Relations encourages a critical, reflective approach to the study of IR theory, while emphasising the many important and interesting things it has to teach us about the complexities and challenges of international politics today"-- Provided by publisher.